Examining natural disaster literacy levels of pre-service geography teachers - Abdullah Türker; Ufuk Sözcü (Journal of Pedagogical Research, 2021)
This paper aims at determining the natural disaster literacy levels of pre-service teachers who will teach the natural geography course. The data in the present study, in which the researchers adopted a survey design conducted on 442 pre-service geography teachers (PGTs), were collected through the Natural Disasters Literacy Questionnaire. As a result, it was determined that the general natural disasters literacy of the PGTs was at a high level, but they were at a moderate level in the behavior dimension, which is one of the components of literacy. It is recommended to include subjects and practices on natural disasters in all education levels, to make all PGTs literate in natural disasters during undergraduate education, and to increase the amount of information and practices on natural disasters in the geography course with legal regulations in the dimension of curricula and textbooks.